High peripheral T cell diversity is associated with lower risk of toxicity and superior response to dual immune checkpoint inhibitor therapy in patients with metastatic NSCLC - Alexandre Reuben; Mehmet Altan; Latasha Little; Jianjun Zhang; Ajay Sheshadri; Hai T Tran; Mara B Antonoff; Stephen G Swisher; John V Heymach; Saumil Gandhi; Natalie Vokes; Ziyi Li; et al. (Journal for ImmunoTherapy of Cancer)
Introduction Despite significant successes, immune checkpoint blockade fails to achieve clinical responses in a significant proportion of patients, predictive markers for responses are imperfect and immune-related adverse events (irAEs) are unpredictable. We used T-cell receptor (TCR) sequencing to systematically analyze prospectively collected patient blood samples from a randomized clinical trial of dual immune checkpoint inhibitor therapy to evaluate changes in the T-cell repertoire and their association with response and irAEs.Methods Patients with immunotherapy-naïve metastatic non-small cell lung cancer (NSCLC) were treated with ipilimumab and nivolumab according to trial protocol (LONESTAR, NCT03391869). Blood samples were systematically obtained at baseline (n=107), after 12 weeks of ipilimumab and nivolumab (n=91), and at the time of grade ≥2 irAEs (n=77). For analysis of T-cell repertoire, we performed immunoSEQ to assess the complementary determining region 3β region of the TCR involved in antigen binding.Results A total of 250 samples from 119 patients were analyzed. Patients who had a response to therapy exhibited greater T-cell diversity at baseline. Interestingly, patients with irAEs demonstrated lower T-cell richness at the time of toxicity compared with those without irAEs.Conclusion Our study highlights the potential impact of peripheral blood T-cell repertoire on clinical response and toxicities from the combination of ipilimumab and nivolumab in patients with metastatic NSCLC. These findings suggest that analysis of peripheral blood T-cell repertoire may help to guide patient selection for treatment with ipilimumab and nivolumab.Trial registration number NCT03391869.